Advanced Approaches, Business Models, and Novel Techniques for Management and Control of Smart Grids - Siano, Pierluigi; Shafie-khah, Miadreza (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The current power system should be renovated to fulfill social and industrial requests and economic advances. Hence, providing economic, green, and sustainable energy are key goals of advanced societies. In order to meet these goals, recent features of smart grid technologies need to have the potential to improve reliability, ﬂexibility, efﬁciency, and resiliency. This book aims to address the mentioned challenges by introducing advanced approaches, business models, and novel techniques for the management and control of future smart grids.